Intestinal Parasitosis among Human Immunodeficiency Virus and Tuberculosis Infected Patients from Dharan, Nepal - Ghimire, Arjun; Rai, Kishor; Khanal, Hemanta (Himalayan Journal of Science and Technology, 2021)
Intestinal parasitic infestation reflects a health threat with patients living with HIV & Tu-berculosis (TB). Parasitic infections caused by protozoa and helminths are the most com-mon infections worldwide. The present study was done to find out the frequency of intes-tinal parasitosis among HIV and Tuberculosis (TB) patients of Dharan total of 53 samples (>15 years) from HIV seropositive patients and 28 samples (>20years) from TB patients were collected in a clean, dry and capped fitted container and subjected to macroscopic and microscopic examination for ova, cyst, adult parasites and or segments of parasites. Stool samples were fixed in a 10% formalin-ether solution. Sedimentation technique, with modified acid-fast (Ziehl-Neelsen) staining method, was performed for opportunistic in-testinal parasites in both patients. Multi-parasitic infection was noted in the study. The overall prevalence of intestinal parasites was found to be 54 (66.67%). This result had shown that the participation of male patients was comparatively higher than female pa-tients. Out of 81 stool samples, 15 (27.78%) G. lamblia, 12(22.22%) E. histolytica, 12 (22.22%) Cryptosporidium parvum, 6 (11.11%), Isospora belli 4 (7.40%) Microspridium, 1(1.85%) Blastocystis hominis, 2(3.70%) and Taenia spp, 2(3.70%). To prevent this infec-tion appropriate health education should be given to the patients concerning disease trans-mission, antiparasitic therapy, personal hygiene, and safe drinking water.